Radiography of the Tax Inspection Activity in the Context of Contemporary Challenges - Andreea-Florentina Crăciun; Raluca-Ioana Răcătăian; Nicoleta-Claudia Moldovan (Ovidius University Annals: Economic Sciences Series, 2022)
This paper maps the influences exerted by the changes related to the period 2016-2021 on the tax inspection activity in Romania, characterized by permanent regulation adaptation, the slow adoption of information technology in public administration, and inefficient crisis management. The data relating to the activity of the National Agency for Fiscal Administration (NAFA) considered in the paper were extracted from the Statistical Bulletins and the Biannual Activity Reports of NAFA. The analysis of contemporary challenges and their effects on the fiscal inspection activity can be found in this study. A detailed trend estimation and correlation analysis between the variables that define the tax activity was made through a model of simultaneous equations using EViews. Our results reveal that the tightening of regulations in specific sectors, the implementation of IT systems in economic activity, and the measures taken in the context of the pandemic are directly reflected in the number of tax inspections and the number of active taxpayers.